Upaya Meningkatkan Hasil Belajar Melalui Penerapan Model Pembelajaran Kooperatif Tipe TGT (Teams Games Tournament) di SMP Negeri 1 Sakra Barat - B Minardiningsih (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
This study aims to determine whether through the application of the TGT cooperative learning model can improve the learning outcomes of the Human Reproductive System, and also to determine the response of students to the application of cooperative learning learning models. The type of research conducted is PTK with a qualitative approach. Research data in the form of learning outcomes obtained in the study as much as 2 cycles. Data on student learning outcomes are collected from the pre-test and post-test scores given by researchers in each cycle. The results of the study showed that the application of the TGT cooperative learning model could improve the learning outcomes of students in class IX.A SMPN 1 Sakra. This can be seen in the percentage increase in learning outcomes in cycle II is greater than cycle I. The average post-test score of cycle I is 64, while the average post-test score of cycle II is 70. Percentage of increase in mastery learning in cycle I students amounting to 56% while the percentage increase in learning completeness of students in cycle II was 85%.